2012
DOI: 10.1016/j.ijrobp.2012.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Radiation Therapy to the Primary Tumor in Patients With Non-small Cell Lung Cancer and Oligometastasis at Diagnosis

Abstract: Purpose We investigated prognostic factors associated with survival in patients with non-small cell lung cancer (NSCLC) and oligometastatic disease at diagnosis, particularly the influence of local treatment to the primary site on prognosis. Methods and Materials From January 2000 through June 2011, 78 consecutive patients with oligometastatic NSCLC (<5 metastases) at diagnosis underwent definitive chemoradiation therapy (≥45 Gy) to the primary site. Forty-four of these patients also received definitive loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 20 publications
(30 reference statements)
8
80
4
Order By: Relevance
“…Aggressive therapy for the primary tumor and metastatic lesions in NSCLC patients with oligometastases may produce better OS [9,10,14]. Our results also showed that radiation to metastatic sites displayed a trend towards improving OS in patients with only bone oligometastases.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Aggressive therapy for the primary tumor and metastatic lesions in NSCLC patients with oligometastases may produce better OS [9,10,14]. Our results also showed that radiation to metastatic sites displayed a trend towards improving OS in patients with only bone oligometastases.…”
Section: Discussionsupporting
confidence: 57%
“…Lopez et al reported that patients who had smaller tumor volumes had longer OS [9]. Our results showed that patients with a GTV <159 cm 3 tended to have longer OS than those with a GTV ≥159 cm 3 .…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The proportion of patients who are recommended to receive regional treatment comprises more than 50% of all patients with oligometastatic disease. For these recommendations, a biologically proven concept does not exist and only in a few cases are these recommendations supported by prospective trials [36,39,40]. Both translational and prospective clinical trials are urgently needed to validate this clinical practice, supported by further advancements in molecular cancer subtyping that will help to define curable oligometastatic disease states [41].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the general opinion is that patients with 1-5 metastases is oligometastases [79, 13]. In general consideration, pharmacotherapy was the main treatment modality, and, radiation to primary tumor not affect survival and should be only given to alleviate symptoms (hemoptysis, cough, pain, and others) in non-oligometastatic Stage IV NSCLC.…”
Section: Introductionmentioning
confidence: 99%